Detection of Novel duck reovirus (NDRV) using visual reverse transcription loop-mediated isothermal amplification (RT-LAMP) - Li, Zhili (Sci Rep, 2018)
Here we present a visual reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for detecting the gene encoding the σB major outer-capsid protein of novel duck reovirus (NDRV). A set of primers, composed of two outer primers, two inner primers and two loop primers, was designed based on the gene of interest. The LAMP reaction was conducted in a traditional laboratory water bath at 65 °C for 50 min. We compared the performance of calcein/Mn(2+) and SYBR Green I dyes, as well as electrophoresis on agarose gel stained with GoldView nucleic acid dye to detect the RT-LAMP-amplified products and all assays could be employed to discriminate between positive and negative specimens in visible or UV light. Our data showed that there is no cross-reaction with other viruses and the RT-LAMP technique displayed high sensitivity for detecting NDRV with a minimal detection limit of 200 fg RNA input. This assay was more sensitive than conventional PCR in detecting NDRV both in natural and experimental infection. In conclusion, the RT-LAMP technique was remarkably sensitive, specific, rapid, simple and profitable for the identification of NDRV.